Análisis térmico-económico de un motor de combustión interna a partir del uso de dos distintos combustibles disponibles comercialmente en el sector del transporte colombiano (2022)
This TIG is part of a research project approved by the Vice President for Science, Technology and Innovation of the Antonio Nariño University. Project No 2022008 entitled: "Development of statistical techniques for the analysis of uncertainty and metrological performance in industrial equipment" seeks to evaluate the metrological reliability of industrial equipment. In this sense, this TIG has as its main objective to know the thermal performance of an internal combustion engine and, likewise, to carry out an economic analysis based on the use of two types of fuels used in the Colombian transport sector, i.e.: regular gasoline and extra gasoline. The main motivation for this study arises from the problems identified in the operation of the UAN combustion engine, which requires knowing the performance parameters from the use of various types of fuels. Additionally, it is expected to use AHP-type multi-criteria methods to carry out the economic analysis of the process. Finally, it is expected that the results of the project will contribute to knowing the operating conditions of the internal combustion engine. Likewise, the publication of scientific articles in a SCOPUS journal is expected within the framework of the research project approved by the VCTI.